Baroque Sovereignty : Carlos de Sigüenza y Góngora and the Creole Archive of Colonial Mexico - More, Anna Herron (Book collections on Project MUSE., 2013)
This book examines the emergence of a creole archive of artifacts, history, and traditions of colonial Mexico, primarily curated by the polymath Carlos de Sigüenza y Góngora. The author posits the centrality of this archive for understanding how a local political imaginary emerged from the ruins of Spanish imperialism.